Pengaruh Daya Tarik Iklan Dan Electronic Word Of Mouth (E-Wom) Terhadap Minat Pengguna Jasa Transportasi Online Grab: Studi pada Mahasiswa/I Universitas Buana Perjuangan Karawang - Raihani Putri, Qory; Savitri, Citra; Pramudita Faddila, Syifa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The emergence of the Grab service in Indonesia is an example of how the contemporary era and globalization have encouraged innovation and change. The business actively uses internet marketing techniques, with a focus on making advertising and electronic word of mouth more attractive to attract users. This research tries to find the impact of advertising attractiveness on e-Wom as well as the impact of user interest in Grab influenced by advertising and electronic word-of-mouth. SmartPLS 4 analysis is used in a research approach with the student population of Buana Perjuangan University, Karawang. By implementing the Slovin formula in the analysis, a sample of 385 respondents was selected with an error rate of 5%. The findings of this study show that e-Wom is strongly influenced by advertising attractiveness, and users' propensity to purchase Grab services is very positively influenced by e-Wom and advertising attractiveness.